COMPETITIVENESS TEXTILE CLUSTER PERU MEXICO - Gutiérrez Huby, Ana María (2011)
This article is a summary of the research study entitled "A comparative study in Peru- Mexico textile cluster in determining competitive strategies" that was developed in 2010 by the author in collaboration with a team of researchers at the University of Guadalajara. This article basically presents the results in comparative terms of the competitive situation of the textile cluster, Peru and Mexico, "Gamarra" and "Zapotlanejo" respectively representing the textile industry in their countries, with the intention of sharing operational aspects of the dynamics existing in both scenarios to maintain or optimize production levels which ultimately allowed the research team's approach their respective competitive strategies for market consolidation in the national projection and international venture.